Laras in Gamelan Music's Plurality - -, Widodo (Harmonia: Journal of Arts Research and Education, 2015)
Coercion, strife, contention, assault, and battle between individuals and groups today have never deserted from the news in mass media. The triggers are selfishness, feeling of self-righteous, overbearing, and a desire to be always comfortable and win, while neglecting differences had by one to another. It is pushed by unwillingness and inability to respect the differences as God's will and grace. Plurality as an inevitability cannot be ignored as well as rejected. Willy nilly, it has to be faced, accepted, and respected as it is. It also needs to be assembled in order to actualize harmony in togetherness as in diversity in Â the musical aspects of traditional Javanese karawitan in gending composition. This paper is a reflection result towards diversity in gending composition which raises beautiful musical alignment in order to reflect the plurality in life and to build harmony.